Cloning and expression of AhpC gene of Mycobacterium avium sub sp. paratuberculosis - PERUMAL, SARAVANA; VIJAYARANI, K; KUMANAN, K; RAMASWAMY, V (The Indian Journal of Animal Sciences, 2012)
The present study was undertaken to amplify, clone and express AhpC gene from Mycobacterium avium sub sp. paratuberculosis (MAP). Primers specific for AhpC gene with restriction enzyme sites, viz. NdeI and XhoI were designed. AhpC gene was amplified using DNA from MAP culture with designed primers by polymerase chain reaction (PCR). An amplicon of size 588 bp was obtained. The AhpC gene was first cloned into TOPO vector pCR2.1 and subcloned into prokaryotic expression vector pET22b. Colony PCR was carried out for the selection of the recombinant clones and further confirmed by restriction enzyme digestion. The recombinant clone was induced with 0.3 mM final concentration of isopropyl-ÃŸ-D-thiogalactopyranoside (IPTG) for the expression of the recombinant AhpC gene. The expressed protein was analysed by 12% SDS-PAGE. As AhpC gene exist as a homodimer, 2 protein fractions of 24 KDa and 45 KDa were obtained after induction. The specificity of the protein was determined by immunoblot analysis with polyclonal MAP antibodies.